Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan Terhadap Profitabilitas pada CV. Sumber Agung Ngawi - Eno Arbiansyah; Dorothea Ririn Indriastuti (Indo Publishing, 2025)
This research was conducted at CV. Sumber Agung Ngawi, East Java. The purpose of this study was to analyze the significance of the influence of cash turnover, receivables turnover, and inventory turnover on profitability at CV. Sumber Agung Ngawi, East Java. The type of data used is quantitative data. The data source used is secondary data. Data collection techniques used observation and interviews. The sampling technique used purposive sampling. Data analysis techniques used in this study are classical assumption tests, descriptive analysis, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (R2). The results of the classical assumption test show that all variables have passed the multicollinearity, heteroscedasticity and normality tests. The t-test results show that Cash Turnover (X1) has a significant effect on Profitability (Y), Accounts Receivable Turnover (X2) has a significant effect on Profitability (Y), and Inventory Turnover (X3) has a significant effect on Profitability (Y). The F-test results show that the regression model used is appropriate in predicting the effect of Cash Turnover (X1), Accounts Receivable Turnover (X2) and Inventory Turnover (X3) on Profitability (Y). The results of the coefficient of determination test (adjusted R2) for this model are 0.839, meaning that the independent influence of X1 (Cash Turnover), X2 (Accounts Receivable Turnover) and X3 (Inventory Turnover) on Y (Profitability) is 83.9%. The remaining (100% - 83.9%) = 16.1% is explained by other variables outside the model